Two‐year outcomes in initial survivors with acute liver failure: results from a prospective, multicentre study. (28th July 2014) - Fontana, Robert J.; Ellerbe, Caitlyn; Durkalski, Valerie E.; Rangnekar, Amol; Reddy, Rajender K.; Stravitz, Todd; McGuire, Brendan; Davern, Timothy; Reuben, Adrian; Liou, Iris; Fix, Oren; Ganger, Daniel R.; et al.
Abstract Background & Aims The long‐term clinical outcomes in initial survivors with acute liver failure (ALF) are not well known. The aim of this study was to provide an overview of the 2‐year clinical outcomes among initial survivors and liver transplant (LT) recipients that were alive 3 weeks after enrolment in the Acute Liver Failure Study Group (ALFSG). Methods Outcomes in adult ALFSG patients that were enrolled between 1998 and 2010 were reviewed. Results Two‐year patient survival was significantly higher in the 262 LT recipients (92.4%) compared to the 306 acetaminophen (APAP) spontaneous survivors (SS) (89.5%) and 200 non‐APAP SS (75.5%) (P < 0.0001). The causes of death were similar in the three groups but the time to death was significantly longer in the LT recipients (P < 0.0001). Independent predictors of 2‐year mortality in the APAP group were a high serum phosphate level and patient age (c‐statistic = 0.65 (0.54, 0.76)), patient age and days from jaundice to ALF onset in the non‐APAP group (c‐statistic = 0.69 (0.60, 0.78)), and patient age, days from jaundice, and higher coma grade in the LT recipients (c‐statistic = 0.74 (0.61, 0.87)). The LT recipients were significantly more likely to be employed and have a higher educational level (P < 0.05). Conclusions Two‐year outcomes in initial survivors of ALF are generally good but non‐APAP patients have a significantly lower survival which may relate to pre‐existing medical comorbidities. Spontaneous survivors with APAP overdose experience substantial morbidity during follow‐up from ongoing psychiatric and substance abuse issues.